Whorled Urothelial Cell Carcinoma: A Neglected Variant. (August 2014) - Patriarca, Carlo; Comperat, Eva; Bollito, Enrico; Ussia, Agazio; Scola, Giovanni; Cavallero, Alessandra; Ferrari, Lucia; Giunta, Paolo; Conti, Giario
Twelve cases of urothelial cell papillary carcinoma with a whorled pattern of growth are described. This variant is reported with clinicopathological correlations and immunohistochemical findings. All cases showed this peculiar and distinctive curlicue histological pattern, ranging from 50% to 100% of the neoplastic population. Despite the disordered/turbulent growth pattern, the cytological grade was uniformly low. All the lesions were Ta staged and no patient experienced progression after transurethral resection, while 2 showed clinical recurrences. The immunophenotype (low p53, high p27, low Ki67, and high GATA3) of the cases contributes to define this rare variant as a low-grade tumor.